Does G-4 Liquidity Spill Over? - Psalida, L. (IMF Working Papers; Working Paper ;, 2011)
The resumption of strong capital flows into emerging markets in mid-2009 brought back the debate over whether pull or push factors are the main determinants. This paper, using panel specifications with alternative measures of global liquidity, asks the question whether G-4 liquidity expansion spills over to the rest of the world. The paper finds strong positive links between G-4 liquidity expansion and asset prices, such as equities, in the liquidity receiving economies, which indicates that the push factor plays an important role in asset prices. Liquidity also has a strong positive link with the accumulation of official reserves and with equity portfolio inflows in receiving economies. Moreover, the association between excess equity returns, excess credit growth, and global liquidity has implications for rising risks to financial stability in the receiving economies.